Penerapan Model Auditory Intellectually Repetition (Air) Terhadap Aktivitas Dan Hasil Belajar Kognitif Siswa Sekolah Dasar - Ungking, Nelly Wedyawati; Gamilina, Pranciska (KEGURU "Jurnal Ilmu Pendidikan Dasar", 2018)
This study aims to assess the application of Auditory Intellectually Repetition (AIR) learning model to the activity and results of cognitive learning math for grade V students of primary school number 2 Sintang, in academic year 2017/2018. It is Quantitative research method. The form of research is quasi experimental design with pretest-posttest control group design. In collecting the data the researcher used measurement, direct observation, observation, indirect and the study documentation techniques.  After analyzing, it was known that activities data amount of 83% the category very high pretest and posttest data and experimental class counted statistically using t-test, with a = 0.05 and dk n1 + n2 - 2 then obtained tcount> ttable = 18,178 > 2,074 it is mean Ha received and Ho rejected.  The conclusion of the research is the learning model of Auditory Intellectually Repetition (AIR) can increase the activity and the result of learning mathematics.